Effects of diet, sulphonylurea group of oral antidiabetic drugs and insülin treatment on blood glucose levels in patients with Type 2 diabetes mell tus (Annals of Medical Research, 2021)
None
Keywords: Type 2 diabetes, diet, gliclazide, acarbose, insulin